2017
DOI: 10.1073/pnas.1616893114
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-derived proangiogenic metabolites of epoxyeicosatrienoic acids

Abstract: Arachidonic acid (ARA) is metabolized by cyclooxygenase (COX) and cytochrome P450 to produce proangiogenic metabolites. Specifically, epoxyeicosatrienoic acids (EETs) produced from the P450 pathway are angiogenic, inducing cancer tumor growth. A previous study showed that inhibiting soluble epoxide hydrolase (sEH) increased EET concentration and mildly promoted tumor growth. However, inhibiting both sEH and COX led to a dramatic decrease in tumor growth, suggesting that the contribution of EETs to angiogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 40 publications
2
52
0
Order By: Relevance
“…Zhang, et al, 2013). A partial hypothesis to explain this is that an angiogenic metabolite of 8,9-EET can be formed by COX enzymes but the metabolite does not form in the presence of COX inhibitors or competing omega-3 lipids (Rand, et al, 2017). The EDPs which cannot form an analogous angiogenic metabolite are inherently antiangiogenic and the EETs, in the presence of celecoxib, are as well.…”
Section: Seh As a Target For Inflammatory Diseasesmentioning
confidence: 99%
“…Zhang, et al, 2013). A partial hypothesis to explain this is that an angiogenic metabolite of 8,9-EET can be formed by COX enzymes but the metabolite does not form in the presence of COX inhibitors or competing omega-3 lipids (Rand, et al, 2017). The EDPs which cannot form an analogous angiogenic metabolite are inherently antiangiogenic and the EETs, in the presence of celecoxib, are as well.…”
Section: Seh As a Target For Inflammatory Diseasesmentioning
confidence: 99%
“…COX is the rate-limiting enzyme in the synthesis of prostaglandins. COX exists both as a constitutively expressed isoform (COX-1) and a regulated isoform (COX-2) ( 74 ). COX-2 enables tumor cells to escape immunological surveillance ( 75 , 76 ).…”
Section: Immunosuppressive Microenvironment In Ecmentioning
confidence: 99%
“…Even though COX-2 was induced by EETs in PDGF-treated VSMCs, EET did not enhance PDGF-stimulated VSMC migration, unlike AUDA ( Figure 4 A,B). Recent studies have shown that 5,6-EET, 8,9-EET, and 11,12-EET, but not 14,15-EET, can be metabolized by COX-2 to produce mitogenic and angiogenic metabolites (e.g., ct-8,9-epoxy-11-hydroxy-eicosatrienoic acid), which are then subjected to sEH metabolism [ 45 , 46 ]. Although their roles in the migration of VSMCs are yet to be elucidated, it seems possible that sEH inhibition by AUDA stabilizes these metabolites, as well as EET, thereby facilitating VSMC migration.…”
Section: Discussionmentioning
confidence: 99%